Capaian standar proses implementasi kurikulum 2013 (studi kasus pada SMA 1, SMA 2 dan SMA 5 sebagai sekolah piloting Kota Balikpapan) - C asmudi (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2017)
This study aims to reveal: (1) process standard achievement (2) obstacles faced by schools (3) strategy to overcome obstacles in the implementation of Curriculum 2013. The method used in this research is qualitative method with observation approach, interview and document study. Data subject; Principals, Vice facility and Curriculum, subject teachers, students and parent representatives. Research result; (1) Principles of learning, (2) Learning Planning, (3) Lesson Plan, covering Introduction, core activities and closing (4) assessment of learning outcomes done with three domains, attitudes, knowledge, and skills of achievement are, (a) SMA N 5; 87.55 (b) SMA N 2; 88.88 and (c) SMA N 1; 94.44, (5) Supervision of learning outcomes is done in four steps; (a) Monitoring, this activity is carried out by the principal and supervisor of the supervisor in each school, (b) supervision of teachers in the class conducted by Subject supervisors, using the instrument, the results of class supervision prepared semester final report, the result of the average teacher is 7.8. Teachers with less than 70 supervision scores, follow-up step by giving specific guidance and priority supervision entry. Implications of implementation of process standards as piloting school drivers improve SKS program as a follow-up channel of optimization of learning process standards in channelling students' academic interests and talents accordingly with its characteristics.